2000
DOI: 10.1021/bi992660q
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Atrial Natriuretic Peptide ANP-C Receptor Is Associated with Alterations in G-Protein Expression in A10 Smooth Muscle Cells

Abstract: Atrial natriuretic peptide (ANP) receptors A and B are guanylyl cyclase receptors, whereas ANP-C receptors are coupled to adenylyl cyclase through inhibitory guanine nucleotide (Gi) protein. ANP has been shown to downregulate ANP-A and -B receptors and cGMP response in various tissues. In the present studies, we have examined the regulation of ANP-C receptor-adenylyl cyclase signal transduction by ANP and [des(Gln(18),Ser(19),Gln(20),Leu(21), Gly(22))ANP(4-23)-NH(2)](C-ANP(4-23)) that interacts specifically wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
(135 reference statements)
2
33
0
Order By: Relevance
“…Our recent data in COS-7 cells transiently expressing NPRA have provided the evidence that its internalization seems to be controlled by sequences located within the carboxyl-terminal domain of this receptor protein (28). The phenomena of receptor-mediated internalization and metabolic processing of ANP through the non-guanylyl cyclasecontaining receptor, NPRC, have been investigated in a number of laboratories utilizing vascular smooth muscle cells, which contain a predominantly high density of endogenous NPRC (35)(36)(37)(38)(39)(40)(41)(42)(43). Early studies of the post-binding events of NPRC were greatly facilitated because of its predominant presence in vascular smooth muscle cells, which are among the important target cells for ANP.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent data in COS-7 cells transiently expressing NPRA have provided the evidence that its internalization seems to be controlled by sequences located within the carboxyl-terminal domain of this receptor protein (28). The phenomena of receptor-mediated internalization and metabolic processing of ANP through the non-guanylyl cyclasecontaining receptor, NPRC, have been investigated in a number of laboratories utilizing vascular smooth muscle cells, which contain a predominantly high density of endogenous NPRC (35)(36)(37)(38)(39)(40)(41)(42)(43). Early studies of the post-binding events of NPRC were greatly facilitated because of its predominant presence in vascular smooth muscle cells, which are among the important target cells for ANP.…”
Section: Discussionmentioning
confidence: 99%
“…NPR-A and NPR-B are membrane guanylyl cyclase receptors, whereas NPR-C does not possess guanylyl cyclase activity. Two different subtypes of NPR-C with molecular mass of 67 and 77 kDa have been identified with a broad range of ligands, including ANP, brain natriuretic peptide, C-type natriuretic peptide, and C-ANP [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] [des(Gln, 18 Ser, 19 Gly, 20 Leu, 21 ; however, C-ANP 4-23 is specific for NPR-C and has no affinity for NPR-A or NPR-B. 8,9 The 77-kDa protein is implicated in ligand internalization as a clearance receptor, 10 whereas 67-kDa protein is coupled to adenylyl cyclase inhibition through inhibitory guanine nucleotide regulatory protein Gi 7,11 or to activation of phospholipase C (PLC).…”
mentioning
confidence: 99%
“…8,9 The 77-kDa protein is implicated in ligand internalization as a clearance receptor, 10 whereas 67-kDa protein is coupled to adenylyl cyclase inhibition through inhibitory guanine nucleotide regulatory protein Gi 7,11 or to activation of phospholipase C (PLC). 12 However, we showed that NPR-C activation by C-ANP [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and resultant decrease in cAMP levels contribute to the activation of phosphatidyl inositol turnover signaling and suggested a cross-talk between NPR-C-mediated adenylyl cyclase inhibition and PLC signaling pathways. 13 The activity of adenylyl cyclase is regulated by 2 guanine nucleotide regulatory proteins (G proteins): Gs (stimulatory) and Gi (inhibitory).…”
mentioning
confidence: 99%
See 2 more Smart Citations